Between the Cross and the Crescent: Marking One’s Territory and Intercultural Coexistence in Orthodox-Muslim Relations in Macedonia - Sekulovski, Goran (Eurostudia)

(untitled) (Le Centre canadien d’études allemandes et européennes, 2018)
This article analyses the complex relations between Orthodox Christians and Muslims in the Republic of Macedonia. Over the last ten years, 350 new mosques and minarets have been built in the country, and nearly as many new churches, monasteries and chapels. As a result, there are presently nearly 2000 churches and 600 mosques in the country, which is equivalent to one church or mosque for every 800 inhabitants. In order to understand the operative logic of these developments, whereby religious communities symbolically mark their territories, we must go beyond the question of landscape and highlight the dynamics of intercultural coexistence through an analysis of public policies on religious matters. These are some of the questions which this article attempts to deal with, attaching equal importance to various areas of study: religious landscape, interculturalism and public policies.